SGLT2 inhibitors: suggestions from the amphibian world - Stefano Michelassi (AboutScience Srl, 2022)
Sodium-glucose cotransporter 2 inhibitors are a class of antidiabetic drugs that inhibit glucose reabsorption in the proximal renal tubules. In many trials these drugs have shown unpredictable major cardio- and nephroprotective properties. Multiple hypotheses have been raised to elucidate the mechanisms underlying the last effects. Some authors suggest they may be due to the contemporary urinary loss of energy (as glucose) and water (by osmotic diuresis). This particular condition could induce metabolic changes resulting in more efficient energetics at cardiac and renal levels and in less oxidative stress. These changes might really be part of a series of evolutionarily conserved metabolic switches that allow organisms to survive in arid habitats with restricted nutrients and water availability, well studied in amphibians and collectively named "estivation".